The impact of CO2 enrichment on fiber dimension and lignocellulose properties of three varieties of kenaf (Hibiscus cannabinus L.) - Khalatbari, Amir Mahdi; Jaafar, Hawa Z. E.; Khalatbari, Amir Ali (Chilean Society of Soil Science, 2014)
The effects of two different carbon dioxide levels on fiber yield, fiber dimension and lignocelluloses properties of three varieties of kenaf (Hibiscus cannabinus L.) namely Fuhong (FH991), V36 and Kohn-Kaen60 (KK60) were assessed in a growth house experiment at faculty of Agriculture, Universiti Putra Malaysia. Seeds were sown in polyethylene bags containing top (loamy soil). Carbon dioxide enrichment treatment started when the seedlings reached four weeks and plants were exposed to 400 and 800 µmol mol-1 of CO2. A factorial experiment was arranged in a split plot using a randomized complete block design (The CO2 chamber is perpendicular to sunrise and sunset) with CO2 levels as the main plot, and different varieties as sub-plot replicated three times. Different CO2 levels had significant impact on fiber dimension, fiber yield and lignocellulose properties of bast and core fiber for all three varieties. Result indicated that increasing CO2 concentration from 400 µmol mol-1 to 800 µmol mol-1 positively affected fiber of all varieties under study. Increase in fiber length and slight reduction in fiber diameter at 800 mol-1 resulted in higher fiber quality for paper production purposes. These results provide significant insights into opportunities for growing of kenaf under enriched CO2 concentration.